FERTILITY BASED ON DEMOGRAPHIC AND SOCIAL ECONOMIC FACTORS IN WOMEN OF REPRODUCTIVE AGE IN BENGKULU PROVINCE (SECONDARY DATA ANALYSIS 2017 IDHS) - Bintang Agustina Pratiwi; Nopia Wati; Oktarianita Oktarianita; Wulan Angraini; Mugia Bayu Raharja (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2023)
The Total Fertility Rate (TFR) of Bengkulu Province is still at 2.31, meaning that there are still Women of Reproductive Age who have children >2. This condition affects the non-fulfillment of basic family needs.  The purpose of this study was to determine the factors causing fertility based on demographic, social, and economic factors in Women of Reproductive Age in Bengkulu Province. This study is a study that uses secondary data from the Indonesian Demographic Health Survey (IDHS) in 2017. The population in this study is 49,250 households nationally. The number of households that were successfully interviewed in Bengkulu Province was 850. Ever married women aged 15-49 years were 809 people. Furthermore, the weighted sample was 364 people, from the weighted sample 274 samples met the criteria. The data analysis used in this study consisted of 3 types of data analysis, that is univariate analysis, bivariate and multivariate analysis. The results showed that there was a relationship between demographic factors, namely maternal age (p = 0.000), and husband's age (p = 0.000) with Women of Reproductive Age fertility. There is a relationship between socioeconomic  factors,  that  is  maternal  education (0.026) with Women of Reproductive Age fertility in  Bengkulu  Province. The  dominant  factor causing fertility  was age at marriage (p = 0.019 and OR = 1.911).